Coping Strategy Psychoeducation to Enhance Work Adaptation Among Internship Participants at PT Laksana Bus Manufaktur - Muthiara Pristita Maharani Putrian; Lisna Jelita; Ramadhani Arya Laksana; Tiara Salsabilla; Gampang Satriyo Raharjo; Talitha Lintang Pertiwi (Sakura Digital Nusantara, 2026)
Global changes and the implementation of Work From Home (WFH) policies require individuals to adapt effectively to evolving workplace dynamics. Internship and fieldwork students transitioning from academic to professional environments often face adaptation challenges. This community service program aimed to enhance participants' understanding of the psychological impacts of changing work systems and adaptive coping strategies through psychoeducation. A one-group pre-test–post-test design was employed involving 23 participants at PT Laksana Bus Manufaktur selected through purposive sampling. Data were collected through observation, supervisor feedback, and pre-test and post-test assessments. Results showed an increase in average scores from 7,74 to 9,35, a 20.8% improvement. However, the absence of a control group limits the extent to which this gain can be attributed solely to the intervention. These findings suggest a preliminary improvement in participants' understanding and may serve as a basis for future studies with more rigorous designs.